1983
DOI: 10.1177/109634808300800105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Educational Skills and Competencies Needed By Beginning Hospitality Managers

Abstract: The need for competent management personnel has created outstanding career opportunities for foodservice and lodging management graduates. This increased demand, however, has also created problems in the development and evaluation of hospitality education. Academic programs in hospitality vary considerably, and there has been little effort to identify competencies for hospitality occupations, especially at the baccalaurate level. The researcher, therefore, undertook this study to develop and assess the educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 4 publications
4
26
0
Order By: Relevance
“…In early competency studies, Mariampolski et al (1980) suggested that technical and human skills are more important to entry-level foodservice managers compared to conceptual skills, while Buergermeister (1983) argued that while technical skills are important, human relations and conceptual management skills are essential for hospitality managers upon graduation. Tas (1988) developed a set of competencies essential for hospitality management trainees based on the perceptions of 75 hotel managers working in the United States.…”
Section: Competency Studies and Hospitality Professionsmentioning
confidence: 98%
“…In early competency studies, Mariampolski et al (1980) suggested that technical and human skills are more important to entry-level foodservice managers compared to conceptual skills, while Buergermeister (1983) argued that while technical skills are important, human relations and conceptual management skills are essential for hospitality managers upon graduation. Tas (1988) developed a set of competencies essential for hospitality management trainees based on the perceptions of 75 hotel managers working in the United States.…”
Section: Competency Studies and Hospitality Professionsmentioning
confidence: 98%
“…Ten categories of general management knowledge emerged with "developing a service orientation" ranked fifth and "customer-feedback skills" ranked ninth. Hsu and Gregory (1995) a General Management, F&B and Lodging The importance of 30 competency statements drawn from Mariampolsky et al (1980), Buergermeister (1983) and Tas (1988) was assessed on a Taiwan sample of hotel managers. Only one out of thirty statements addresses the guest and relates to "resolving guest problems quickly, efficiently and courteously" Breiter and Clements (1995) Hospitality Graduate Skills A survey of hospitality recruiters regarding important skills for new graduates.…”
Section: Author(s)mentioning
confidence: 99%
“…More specifically, in spite of a number of models developed for hospitality, there seems to be a limited focus on service-specific leadership behaviors (i.e., those that would facilitate customer satisfaction). Despite identification of the importance of guest satisfaction principles in Buergermeister's (1983) seminal study, the customer seems to be ancillary in many studies. As competition increases, leaders who can drive the highest levels of service quality with fewer resources may be essential for organizational success in hospitality and tourism.…”
Section: Introductionmentioning
confidence: 97%
“…Though the roots founded much earlier (Morris, 1973;Mariampolski et al, 1980;Buergermeister, 1983), from the seminal study of Tas (1988) onwards, many studies on hospitality management competencies with their various aspects, yet not ferreted out enough, were carried out up to the very recent. This study, distinctively, (1) aims to discover the current competencies of hotel managers actually demanded by the industry in Turkey.…”
Section: Purpose and Value Of The Papermentioning
confidence: 99%